Ordinances of the Mayor, Aldermen and Commonalty of the City of New York, in Force January 1, 1881; Adopted by the Common Council and Published by Their Authority 214-215 (1881) - (:unkn) unknown (My University, 1881)
ch. 8, art. 27, § 264: And persons to whom permits shall have been issued, as hereinafter provided, who shall have in his possession within the city of New York a pistol of any description concealed on his person, or not carried openly, shall be deemed guilty of a misdemeanor, and shall be punished, on conviction by a fine not exceeding ten dollars, or, in default of payment of such fine by imprisonment not exceeding ten days.
Keywords: CARRY - CONCEALED